Attributing Climate vs. Land-Cover Effects on Watershed Hydrology and Water Quality: A Systematic Review of Modeling and Statistical Frameworks (West Science Interdisciplinary Studies, 2025)
Climate change and land-use/land-cover (LULC) dynamics jointly reshape watershed hydrology and water quality, yet their relative contributions remain difficult to isolate across regions, indicators, and methods. This systematic review synthesizes 28 peer-reviewed studies (2000–2025) that explicitly attribute or partition climate and LULC effects on streamflow, water yield, evapotranspiration, baseflow, and multiple water-quality indicators (e.g., nutrients, sediments, dissolved organic matter, salinity/alkalinity, and contaminant mixtures). Studies were grouped into four synthesis themes: (i) conceptualizations and study designs, (ii) process-based and hybrid modeling frameworks, (iii) statistical and decomposition approaches, and (iv) cross-context patterns and water-quality attribution. Across the evidence base, attribution outcomes are strongly conditioned by methodological choices—especially baseline definition, construction of climate-only and LULC-only counterfactuals, spatial and temporal scale, and the metric used to express contributions (e.g., scenario contrasts, sensitivities, or variance explained). Long-term water-balance responses are often attributed primarily to climate forcing, while water-quality outcomes are more frequently attributed to LULC and direct anthropogenic pressures, with climate acting as a key modulator of transport pathways and exposure. We conclude that robust climate–LULC attribution requires explicit counterfactual design, integrated use of process-based and data-driven frameworks, explicit representation of interactions, and routine uncertainty analysis to support context-sensitive watershed management and climate adaptation.